Penerapan Metode Eksperimen untuk Meningkatkan Motivasi Belajar Siswa - Fitran Sari (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title:  The Implementation of Experiment Method to Improve Student’s Learning Motivation].   The purpose of this study was to improve the learning motivation of Learners of SMP Negeri 3 Mataram using the experimental method. This research is a classroom action research model of Kemmis and Taggart consisting of three cycles. The stages of each cycle consist of the planning stage, the stage of action, the stage of observation, the stage of reflection. The research implementation subjects were class VIII-3 students, amounting to 29 people on simple aircraft material. The results showed that students' learning motivation in the first cycle obtained an average score of 56.25% consisting of 50% attention, relevance 40%, confidence 75% and satisfaction 60%. Cycle II the average score of students is 68.75% consisting of 72% attention, 78% relevance, 60% confidence and 65% satisfaction. The third cycle average score of 83.27% consisted of 84.16% attention, relevance 80.68%, confidence 84.55% and satisfaction 83.55%. From the results of this study, it can be concluded that the application of experimental methods can increase students' learning motivation in class VIII-3 on Simple Plane material.